Oral melatonin administration improves the objective and subjective sleep quality, increases 6-sulfatoxymelatonin levels and total antioxidant capacity in patients with fibromyalgia - Castaño, M. Yolanda; Garrido, Maria; Delgado-Adámez, Jonathan; Martillanes, Sara; Gómez, M. Ángeles; Rodríguez, Ana Beatriz (Journal of Applied Biomedicine, 2018)
Background/objective.Chronic pain, sleep disturbances and oxidative stress are implicated in the pathogenesis of fibromyalgia. The aim of this study was to assess the effect of melatonin supplementations on sleep quality, 6-sulfatoxymelatonin (aMT6-s) levels, as well as urinary and serum total antioxidant capacity (TAC) in patients with fibromyalgia. Methods. Thirty three patients carried out the full study. A baseline period (10 days) was included in the experimental design to collect information about patients' initial status. Then, patients took different doses of melatonin, during 10 consecutive days each. Placebo was given during 10 days either before or between melatonin doses. Objective sleep quality was recorded by actigraphy whereas subjective sleep quality was measured by The Pittsburgh Sleep Quality Index. Quantification of aMT6-s and TAC was achieved by ELISA and colorimetric assay kits, respectively. Results. Six out of seven sleep parameters evaluated by actigraphy were improved after the intake of melatonin as well as the subjective sleep quality. All the biochemical parameters measured were also elevated after the melatonin administration. Conclusion The daily intake of melatonin improved the sleep quality, increased the aMT6-s levels and the total antioxidant capacity in patients with fibromyalgia.
Keywords: aktigrafie; 6-sulfatoxymelatonin; Antioxidants; biologické markery; Melatonin; Biomarkers; Sleep Wake Disorders; lidé; Fibromyalgia; poruchy spánku a bdění; bolest; Actigraphy; spánek; melatonin; antioxidancia; Sleep; fibromyalgie; Pain; Humans